Can Neurotypical Individuals Read Autistic Facial Expressions? Atypical Production of Emotional Facial Expressions in Autism Spectrum Disorders. Issue 2 (6th June 2015) - Brewer, Rebecca; Biotti, Federica; Catmur, Caroline; Press, Clare; Happé, Francesca; Cook, Richard; Bird, Geoffrey
Abstract : The difficulties encountered by individuals with autism spectrum disorder (ASD) when interacting with neurotypical (NT, i.e. nonautistic) individuals are usually attributed to failure to recognize the emotions and mental states of their NT interaction partner. It is also possible, however, that at least some of the difficulty is due to a failure of NT individuals to read the mental and emotional states of ASD interaction partners. Previous research has frequently observed deficits of typical facial emotion recognition in individuals with ASD, suggesting atypical representations of emotional expressions. Relatively little research, however, has investigated the ability of individuals with ASD to produce recognizable emotional expressions, and thus, whether NT individuals can recognize autistic emotional expressions. The few studies which have investigated this have used only NT observers, making it impossible to determine whether atypical representations are shared among individuals with ASD, or idiosyncratic. This study investigated NT and ASD participants' ability to recognize emotional expressions produced by NT and ASD posers. Three posing conditions were included, to determine whether potential group differences are due to atypical cognitive representations of emotion, impaired understanding of the communicative value of expressions, or poor proprioceptive feedback. Results indicated that ASD expressions were recognized less well than NT expressions, and that this is likely due to a genuine deficit in the representation of typical emotional expressions in this population. Further, ASD expressions were equally poorly recognized by NT individuals and those with ASD, implicating idiosyncratic, rather than common, atypical representations of emotional expressions in ASD. Autism Res 2016, 9: 262–271 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.